Integration of Information Communication Technology Instructional Resources on Students' Motivation and Achievement in Chemistry Practical in Secondary Schools in Kenya. - Munene, Titus Sifuna; Masibo, Edwin N.; Mutsotso, Stanley N. (Journal of Education and Practice, 2023)
Purpose: The purpose of this study was to investigate the influence of integration of ICT instructional resources on learners' motivation and achievement in chemistry practical in secondary schools in Kenya. The objective of this study was to establish the perception of teachers and learners towards use of ICT instructional resources in teaching and learning of chemistry practical in secondary schools; Methodology: Descriptive survey design and quasi experimental research design were utilized in this study. The target population was teachers of chemistry; form three learners and heads of institutions in the secondary schools in the Bungoma County. Stratified random sampling was used to select the schools from which respondents were chosen, the main stratum was the category of schools according to the Ministry of Education, Science and Technology. Simple random sampling was applied to select chemistry teachers, and learners in the sampled schools. Data was collected using questionnaires, and work sheet. Data was analyzed using descriptive and inferential statistics. Findings: It was perceived that integration of ICT resources led to motivation of both teachers and learners in classroom instruction. There was improved performance in chemistry practical with the use of ICT resources. The teachers and learners were motivated when ICT was utilized in teaching and learning of chemistry practical Unique Contribution to Theory and Practice: The conclusion drawn from these findings is that integration of ICT has led to increased teachers' and learners 'motivation and achievement. Moreover, the policy makers would be informed by this research to formulate the policies that will provide direction and ensure quality of application of ICT to knowledge and practice. The Competency Based Curriculum would apply ICT which then be used to replace the need for realia. The recommendations made from this study are that heads of institutions should be good managers of ICT to ensure that they benefit both teachers of chemistry and learners.